2013
DOI: 10.4238/2013.march.15.3
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variability in populations of Centris aenea (Hymenoptera, Apidae), a crop-pollinating bee in Brazil

Abstract: ABSTRACT. Centris spp are oil-collecting solitary bees that are valuable pollinators of crops such as Brazil nut, cashew, and acerola. We investigated the genetic variability of populations of C. aenea in the northeastern region of Brazil. Total DNA was extracted from 59 individuals from 6 locations in the States of Pernambuco and Bahia and a 600-650-bp fragment of the mitochondrial COI/COII region amplified by PCR, followed by digestion with the restriction enzymes DraI and SspI. PCR-RFLP analysis revealed ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(40 reference statements)
1
0
0
Order By: Relevance
“…This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015). Moreover, the gene flow between the two distinct groups (BCIN and CU) recognized in the haplotype network may be affected by Serra do Mar, a mountain range across the Atlantic rainforest in the coastal areas from Southeastern towards Southern Brazil (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 76%
“…This same scenario and biological interpretation have been commonly reported for several eusocial bee species (Yanega 1990;Francisco and Arias 2009;Brito and Arias 2010;Bonatti et al 2014;Francisco et al 2016b). Primitively eusocial and solitary bees are generally not philopatric (Kim et al 2008;Francisco et al 2016a;Rosa et al 2016;Luna-Lucena et al 2017;Toledo et al 2017), but some exceptions have been reported (Ferreira et al 2013;López-Uribe et al 2014Penha et al 2015). Moreover, the gene flow between the two distinct groups (BCIN and CU) recognized in the haplotype network may be affected by Serra do Mar, a mountain range across the Atlantic rainforest in the coastal areas from Southeastern towards Southern Brazil (Figures 1 and 2).…”
Section: Discussionsupporting
confidence: 76%